PERJUDIAN DALAM BALAP LIAR SEBAGAI BENTUK RATIONAL CHOICE (STUDI PADA 5 PELAKU BALAP LIAR DI KOTA PANGKALAN KERINCI KABUPATEN PELALAWAN) - Nurfebrian, Ulfa; Riky Novarizal, (Sisi Lain Realita, 2023)
Illegal racing cannot possibly be separated from the act of betting or gambling. Usually a group in wild racing will carry out betting actions with other wild racing groups. Usually those who place bets will reach an agreement with other players or gamblers by gathering at a location agreed upon by both parties. In this research the problem will be reviewed using rational choice theory. This research was carried out using qualitative methods with a descriptive research type with the main research data obtained through interviews with illegal racing perpetrators, the surrounding community and the Pelalawan Police. Based on the results of interviews that have been conducted, it can be concluded that gambling carried out in illegal racing events is difficult to reveal and prove, where gambling is carried out neatly and covertly, where the police have difficulty finding evidence to prosecute perpetrators of illegal racing gambling. In dealing with illegal racing, the Pelalawan Police carried out several methods, namely conducting outreach to schools regarding the risks associated with illegal racing on the streets, providing knowledge about traffic regulations to schools, and carrying out routine patrols in various locations. Illegal racing often occurs and provides sanctions to those caught carrying out illegal racing.